2016
DOI: 10.1002/ange.201610491
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism‐Based Fluorogenic trans‐Cyclooctene–Tetrazine Cycloaddition

Abstract: The development of fluorogenic reactions which lead to the formation of fluorescent products from two nonfluorescent starting materials is highly desirable,b ut challenging.R eported herein is an ew concept of fluorescent product formation upon the inverse electron-demand Diels-Alder reaction of 1,2,4,5-tetrazines with particular trans-cyclooctene (TCO) isomers.Insharp contrast to knownfluorogenic reagents the presented chemistry leads to the rapid formation of unprecedented fluorescent 1,4-dihydropyridazines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Indeed, during experimentation with various 1,2,4,5‐tetrazines we found that tetrazine derivative 1 a , bearing a p ‐dimethylamino substituent, forms a fluorescent product when combined with equatorially hydroxy‐substituted TCO 2 a (eqTCO). As we have previously reported, the same derivative leads to fluorescent products, with different photophysical properties, upon reaction with the corresponding axially hydroxy‐substituted TCO 2 b (axTCO, Figure B and C). We ascribed the formation of the two different fluorescent species to the production of different tautomers of the dihydropyridazine core (Figures S1 and S2 in the Supporting Information).…”
Section: Figuresupporting
confidence: 62%
See 1 more Smart Citation
“…Indeed, during experimentation with various 1,2,4,5‐tetrazines we found that tetrazine derivative 1 a , bearing a p ‐dimethylamino substituent, forms a fluorescent product when combined with equatorially hydroxy‐substituted TCO 2 a (eqTCO). As we have previously reported, the same derivative leads to fluorescent products, with different photophysical properties, upon reaction with the corresponding axially hydroxy‐substituted TCO 2 b (axTCO, Figure B and C). We ascribed the formation of the two different fluorescent species to the production of different tautomers of the dihydropyridazine core (Figures S1 and S2 in the Supporting Information).…”
Section: Figuresupporting
confidence: 62%
“…The first reaction step of inverse‐electron‐demand Diels–Alder (iEDDA) cycloaddition between a 1,2,4,5‐tetrazine and a dienophile involves the formation of a tetraazabicyclic system, which, after a retro‐Diels–Alder reaction and extrusion of molecular nitrogen, is transformed into a 4,5‐dihydropyridazine (Figure A). This can further isomerize to the corresponding 1,4‐dihydropyridazine through, for example, addition and elimination of a water molecule or alternatively through intramolecular interaction with an appropriately placed heteroatom substituent on the TCO . The initially formed 4,5‐dihydropyridazine heterocyclic core is a unique π‐conjugated system formed upon reaction between tetrazines and all TCO derivatives.…”
Section: Figurementioning
confidence: 99%
“…There are further developments in the tetrazine Diels−Alder reagents where these can be tuned according to pendent groups. 55 Unfortunately these initial cyclopropene photo-cross-linkers caused high nonspecific background labeling. 33 A further example of live-cell imaging was conducted with the most advanced clinical Aurora kinase cell cycle inhibitor, MLN8237.…”
Section: Aliphatic Diazirine Building Blocks and Functional Group Int...mentioning
confidence: 99%
“…[33][34][35] 4-Pyridyl-Tz have previously been used for the design of fluorogenic probes. [36] However, so far there is no comparative data on the IEDDA reaction kinetics of 2-pyridyl-and 4pyridyl-tetrazines. Therefore, we selected a series of phenyl (Ph), 2-pyridyl (2Pyr), 3-pyridyl (3Pyr), and 4-pyridyl (4Pyr) substituted Tz (Fig.…”
Section: Introductionmentioning
confidence: 99%